Realistic g-factor and k.p parameters in III-V semiconductors and prediction of semiconductors layered materials - Bastos, Carlos Maciél de Oliveira (2019)
Semiconductor devices have today an important impact on the contemporary world, with a large number of applications ranging from LEDs to mobile phone chips. The development of new electronic devices needs the control of the electronic structure achieved with new experimental techniques. For this reason, a fundamental issue on this area is the understanding of the electronic structure of the materials that compose such devices. An example is the fact that spintronic devices need a disequillibrium between the spin-up and spin-down distributioins, with a difference of few millieletronvolts between them. Today, only a small group of theoretical methods can achieve the precision needed to guide the development of these new devices. In addition, with the control of growth temperatures and pressures, it is possible to obtain metastable phases of the same material, increasing the spectrum of possible choices. In this PhD project, we propose a theoretical approach that combines two of the most used methods used in the electronic structure calculations, the density functional theory and the k·p method, connecting them via a fitting method that was developed and tuned during its execution period. To test our approach and the fitting method, we have applied it to the zincblende GaAs phase, comparing our theoretical predictions with experimental data, proving the effectiveness of our approach. Extending the application to other III-V zincblende phase semiconductors, we reviewed the k·p parameters, the effective masses and the effective g-factors for these materials. In addition, we investigated transition metal dichalcogenides, which form stratified materials and may form two-dimensional structures, and are possibly semiconductor materials. We investigated three polymorphic phases of 27 materials, predicting their structural, electronic and elastic properties. We also investigated an important trend we found between the charge transferred from the metal to the chalcogen and the energy required to isolate a single layer, proposing a mechanism that explains this effect. In conclusion, we proposed a new theoretical approach, which we applied to III-V semiconductors, and investigated the existence of new semiconductor materials among transition metal dichalcogenides. This PhD project contributes to the increasing of the accuracy of theoretical approaches, with consequences for the development of new semiconductor devices and for the understanding of physical phenomena involving these materials.